O Belo e suas torcidas: um estudo comparativo sobre as formas de pertencimento que cercam o Botafogo da Paraíba - Carvalho, Phelipe Caldas Pontes (2019)
The research dialogued more strongly with three distinct groups of fans of the Botafogo of Paraíba Soccer Team with the objective of carrying out a comparative study on them. The aim was to show that what the media, certain government institutions, police forces, and others, generically call "football fans of the same club" is never a unity, never something homogeneous, free of internal tensions or rivalries. On the contrary, the different fan identities surrounding the same club will create their own territories, their own anthropological places, their own relations of alliances and rivalries that will be constantly being mediated, reinforced and modified depending on the context. The Botafogo-PB fan base, therefore, always thought of in the plural, were analyzed from their differences, their borders, their alterities, thus presenting an extremely heterogeneous reality, quite different from the one commonly touted. Finally, the dissertation was written after almost two years of ethnographic research, with the field of research being extended as the work developed. It started at the Almeidão Stadium and in its surroundings, accompanying the fans, talking with them amid the ritual of games in their home field; then it took over João Pessoa, observing the circulations of these fans by the host city of the analyzed club; and in a third moment the fan was thought beyond his own city, when trips were made with these distinct groups to accompany games outside João Pessoa and even outside the state of Paraíba.